Hypercalcemia after discontinuation of long-term denosumab treatment. Issue 7 (July 2016) - Koldkjær Sølling, A.; Harsløf, T.; Kaal, A.; Rejnmark, L.; Langdahl, B.
Abstract Summary Denosumab is used for treatment of osteoporosis. We present a case report of hypoparathyroid hypercalcemia and increased bone turnover associated with discontinuation of treatment for 10 years with denosumab. There is a need for evidence-based guidelines on discontinuation of long-term denosumab treatment to avoid side effects and preserving anti-fracture efficacy. Purpose Denosumab is commonly used as an anti-resorptive agent for the treatment of osteoporosis. After discontinuation of denosumab, however, bone resorption increases again, and the bone mass gained during therapy is rapidly declining. Thus, treatment with denosumab is considered to be reversible. Methods We present a case report of asymptomatic hypoparathyroid hypercalcemia in a patient who discontinued long-term treatment with denosumab. Results A 67-year-old woman with osteoporosis was treated with denosumab 60 mg subcutaneously every 6 months from 2004 to 2014. She received the last injection in May 2014. Routine biochemistry in November 2014 showed increased s-ionized calcium (I-Ca) 1.64 mmol/L (1.18–1.32 mmol/L) and suppressed p-parathyroid hormone (PTH) 1.6 pmol/L (1.6–6.9 pmol/L). The patient was extensively examined, but no underlying disease was found. In January 2015, the patient began treatment with alendronat 70 mg weekly. In April 2015, serum levels of type 1 collagen C-terminal cross-linked telopeptide, procollagen type 1 N-terminal propeptide and bone-specific alkaline phosphatase were still markedly elevated. From then on, I-Ca and PTH normalized and the bone turnover markers (BTM) decreased. Conclusion In this case report, we describe increased BTMs and hypercalcemia associated with discontinuation of 10 years treatment with denosumab. The increase in BTMs is assumed to be temporary and normalization is expected. Since denosumab is commonly used, there is an urgent need for evidence-based guidelines on discontinuation of long-term treatment, avoiding side effects and preserving anti-fracture efficacy.